Answer :

We have,


ho(gof)(x)=h(gof(x))=h(g(f(x)))


= h(g(2x)) = h(3(2x) + 4)


= h(6x + 4) = sin(6x + 4) x N


((hog)of)(x) = (hog)(f(x))= (hog)(2x)


=h(g(2x))=h(3(2x) + 4)


=h(6x + 4) = sin(6x + 4) x N


This shows, ho(gof) = (hog)of


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Fill in theMathematics - Exemplar

Let f : [2, ∞) <sMathematics - Exemplar

Let f : N Mathematics - Exemplar

Fill in theMathematics - Exemplar

Let f :R →<Mathematics - Exemplar

Let f : [0, 1] <sMathematics - Exemplar

Which of the follMathematics - Exemplar